Stomata Characterization of Native Dendrobium in Liwa Botanical Garden - Wahyuningsih, Sri; Mahfut, Mahfut; Anbiya, Lulu (Pandawa Institute, 2026)
Dendrobium is one of the most commonly collected native orchid genera at the Liwa Botanical Garden, Lampung, Indonesia. In its conservation efforts, the identification of native orchid species through anatomical characterization is essential. The aim of this research is to identify the native Dendrobium species collection at the Liwa Botanical Garden based on stomatal anatomical characteristics and to confirm these results with previous morphological and molecular characterization. The research steps involved the collection of leaves from 19 Dendrobium accessions at the Liwa Botanical Garden, while the anatomical characterization was conducted by preparing paradermal sections to microscopically observe the stomata. The main anatomical characteristics observed included stomatal aperture width, stomatal length, stomatal width, number of stomata, stomatal density, and stomatal index. The results of the study show that, overall, the stomatal aperture width is 2.88 μm, stomatal length is 12.38 μm, stomatal width is 12.58 μm, stomatal density is 29 stomata/mm², and stomatal index is 0.061%. Phenetic analysis based on the dendrogram divided the different native Dendrobium samples into two clusters (A and B) with similarity indices of 1.60 and 0.90, and PCA values (0.170 and 0.044) were found to be greater than 0.02, indicating the contribution of each group. The PCA value of 0.170 reflects the influence of stomatal area, whereas 0.044 reflects the influence of stomatal aperture width, stomatal index, and stomatal density. The anatomical characterization results show a correlation with the identification outcomes based on morphological and molecular characteristics. Furthermore, these findings can serve as a recommendation for the identification of native orchid species and provide a basis for the conservation efforts of native Dendrobium at the Liwa Botanical Garden, Indonesia.